Inclusive Education and the Girl child in Contemporary Nigerian Society: Counselling Implications - Ugboha, Grace Onyowo; Namo, Ibuebue Sarah (NIU Journal of Social Sciences, 2019)
The study investigated inclusive education and the girl child in contemporary Nigerian society, counselling implications. Three research questions and hypotheses were raised as a guide to the study by using survey design. An instrument titled â€œQuestionnaire for Inclusive Education and the Girl Child in Contemporary Nigerian Society (QIEGCCNS)â€ was designed and used to obtain appropriate results for this study. 100 female students from 20 public secondary schools in Jos metropolis were sampled using simple random sampling technique. The research questions were answered using simple percentages while t-test was using to test the hypotheses. The population of the study comprised of 1,200 respondents. The result showed that the inclusive education helps in increasing the girl childâ€™s self-esteem and self-confidence if properly implemented. Also, it showed the differences in scores on factors militating against inclusive education in Nigeria. The study therefore made some recommendations, such as provision of adequate and effective use of technical equipment. Counselling strategies such as, modeling, cognitive restructuring, collaborative learning, transactional analysis and individualized counselling are found to be very useful in inclusive education.  Keywords : Inclusive Education, Girl Child, Contemporary Nigerian Society, Counselling.